2022
DOI: 10.3389/fmed.2022.965562
|View full text |Cite
|
Sign up to set email alerts
|

Frailty in the context of COVID-19 pandemic: A life-threatening condition

Abstract: The pandemic outbreak of coronavirus disease 2019 (COVID-19) has caused emerging challenges for healthcare systems regarding the assistance to the older adult population which, added to the increased life expectancy, may be exposing frail older adults to an increased risk of unfavorable health outcomes. Frailty has a pathogenesis of multifactorial etiology and is defined as a condition characterized by progressive decline in physiological function, weakness, decreased strength, and reduced resilience to stress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 52 publications
0
9
0
Order By: Relevance
“…It Italy, a particularly critical resistance rates are observed for Klebsiella pneumoniae to amoxicillin-clavulanic acid (57.2%) and piperacillin-tazobactam (45.8%), to third generation cephalosporins (> 50%) and to carbapenems (28.7% for meropenem) [ 14 ]. A recent review showed that in the context of COVID-19, frail older adults accounted for approximately 51% of hospitalized patients with confirmed cases and elevated risk of in-hospital mortality [ 5 ]. An American survey based on 50,419 respiratory samples demonstrates how even though the overall median age of the SARS-CoV-2-positive patients was 45 years, the bacterial co-infections were significantly higher in the older age group (60 + years) when compared to any other age group [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It Italy, a particularly critical resistance rates are observed for Klebsiella pneumoniae to amoxicillin-clavulanic acid (57.2%) and piperacillin-tazobactam (45.8%), to third generation cephalosporins (> 50%) and to carbapenems (28.7% for meropenem) [ 14 ]. A recent review showed that in the context of COVID-19, frail older adults accounted for approximately 51% of hospitalized patients with confirmed cases and elevated risk of in-hospital mortality [ 5 ]. An American survey based on 50,419 respiratory samples demonstrates how even though the overall median age of the SARS-CoV-2-positive patients was 45 years, the bacterial co-infections were significantly higher in the older age group (60 + years) when compared to any other age group [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…This highlights how it is necessary to carry out a comprehensive geriatric assessment (CGA) to evaluate the real state of frailty in older persons affected by infectious diseases and for clinical-decision making in frail older people often affected by MDR. For example, a recent meta-analysis highlights the impact of frailty in older adults hospitalized with COVID-19, showing that frail COVID-19 patients have an increased risk of short-term mortality compared to non-frail patients affected by COVID-19 [ 5 ]. A large meta-analysis indicated that 7% of hospitalized COVID-19 patients had a bacterial co-infection that increases to 14% in studies that only included ICU (intensive care unit) patients [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…In fact, some large prospective cohorts have discussed that such data, that is, frailty, daily‐life activities, could plausibly influence mortality rate of COVID‐19, particularly in elderly patients. 34 , 35 Since the data of our study lacks such information regarding activity of daily life or frailty, we could have overlooked its potential role in impacting the 28‐day mortality in patients; so future studies are needed to shed light on the matter.…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that the COVID-19 pandemic has influenced this fact. 13,27 Likewise, it should be noted that the death can also be related to advanced age, exacerbations of the underlying pathology or other complications that reduce the effect of antifungal treatment on mortality.…”
Section: Discussionmentioning
confidence: 99%
“…It must also be clarified that we have not found the reason that justifies younger age and less comorbidity during the second period. It is possible that the COVID‐19 pandemic has influenced this fact 13,27 . Likewise, it should be noted that the death can also be related to advanced age, exacerbations of the underlying pathology or other complications that reduce the effect of antifungal treatment on mortality.…”
Section: Discussionmentioning
confidence: 99%